Good experiences of smart green cities for sustainable green development and democratization - Đorđević, Snežana (Napredak, 2022)
The subject of this paper is the review of good practice of smart green cities in the use of IT applications forproviding public services (including the resolution of ecological issues),coping with climate change and green energy affirmation.A particularly important aspect is the analysis of the coproduction,i.e. of active involvement of citizens through the application in the policy creation process,the preparation of public services package custommade for the community needs as a form of democratization of the society.Good experiences of smart cities are an excellent lesson for Serbia and its cities.The methods used in this paper are the analyses and syntheses of the papers from this field,the analyses of the good method of using IT packages in certain European cities,the creation of good measurement instruments for monitoring microclimate change due to global warming in German and British cities,the study of green energyaffirmation in the Belgian urban district,and comparison with the manner of treating these topics in Serbia. The expected contribution of this paper is the insight into some good practices and indicating the opportunity for our country and cities to take over and apply some of this useful knowledge,skills and instruments for the welfare of our citizens and community.
Keywords: smart cities; coproduction; public policies and services; ecology; green energy